Analisis Asosiasi Merek dan Pengaruhnya pada Keputusan Pembelian Konsumen Studi Kasus pada Ramayana Departemen Store - BTM - Mubarak, Mumuh Mulyana (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research is based on three questions: (1) How is consumer behaviour in buying products ar Ramayana Department Store? (2) What variables are dominant and having chances to be expanded? (3) What brand association do cunsumers have in their mind concering Ramayana Department Store?. Analysis carried out by this research is Respondent Characteristic Analysis and Brand Association Analysis. The result of this research show that competitive price, discount, store location, product selection, and transportation in togetherness manner are able to shape brand association in behalf of Ramayana Department Store â BTM Bogor. The five attributes mentoned above have been internalized in consumersâ mind to depict Ramayana Department Store â BTM Bogor. Keyword: Consumer Behaviour;